2008
DOI: 10.1152/ajpendo.00507.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term intralipid infusion on the immune response during low-dose endotoxemia in humans

Abstract: Novel anti-inflammatory effects of insulin have recently been described, and insulin therapy to maintain euglycemia suppresses the plasma levels of free fatty acids (FFA) and increases the survival of critically ill patients. We aimed to explore the effect of short-term high levels of plasma FFA on the inflammatory response to a low dose of endotoxin. Fourteen healthy male volunteers underwent the following two trials in a randomized crossover design: 1) continuous infusion of 20% Intralipid [0.7 ml·kg−1·h−1(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 76 publications
(81 reference statements)
5
64
0
Order By: Relevance
“…LPS exposure induced an increase in plasma levels of TNF-a, IL-6 and neutrophil count. 35 NGAL was significantly higher in patients with type 2 diabetes compared with that in subjects with NGT. Interestingly, we have also found an inverse association between circulating NGAL and insulin secretion, which is in line with the higher NGAL concentration in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 74%
“…LPS exposure induced an increase in plasma levels of TNF-a, IL-6 and neutrophil count. 35 NGAL was significantly higher in patients with type 2 diabetes compared with that in subjects with NGT. Interestingly, we have also found an inverse association between circulating NGAL and insulin secretion, which is in line with the higher NGAL concentration in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 74%
“…Lipid infusion has also been shown to increase circulating cytokines and in turn induce a proinflammatory status and insulin resistance (33). It has been proposed that saturated FAs can activate the innate immune system and inflammatory pathways via binding to toll-like receptor (TLR)4, which in turn leads to an increase in myocellular ceramide content, which will lead to insulin resistance by direct inhibition of Akt (23).…”
Section: Discussionmentioning
confidence: 99%
“…Erridge et al [38] also identified that fat intake leads to increase of LPS levels in human bloodstream. In addition, intra-lipid infusion significantly pronounced systemic inflammatory response to LPS [39]. In fact, immune system homeostasis can be challenged by continuous external insults, such as SFA-rich diets, pathogen-associated molecular patterns (i.e.…”
Section: Figmentioning
confidence: 99%